Scattering theory with the Coulomb potential - Kadyrov, Alisher; Bray, Igor; Mukhamedzhanov, A.; Stelbovics, Andris (IOP, 2009)
Basic features of a new surface-integral formulation of scattering theory are outlined. This formulation is valid for both short-range and Coulombic long-range interactions. New general definitions for the potential scattering amplitude are given. For the Coulombic potentials the generalized amplitude gives the physical on-shell amplitude without recourse to a renormalization procedure. New post and prior forms for the amplitudes of breakup, direct and rearrangement scattering in a Coulomb three-body system are presented.